Social-psychological adjustment of ex-servicemen to civilian life - Yablonska, Tetiana; Dembytska, Natalia; Vus, Viktor (Social Welfare: Interdisciplinary Approach, 2017)
Social-psychological adjustment of ex-servicemen to civilian life after returning home from combat zone was analyzed in this paper. The authors used a dialectical subjective approach analysing the ability to cope with traumatic experiences of warfare. A theoretical model of social-psychological adjustment was designed, an empirical research was conducted, the factors that facilitate social-psychological adjustment: consistent, coherent ideas about peaceful life, self and others, emotional stability, commitment to social values, self-awareness, a sense of self-fulfilment, social behaviour, peaceful conflict resolution, job satisfaction, relationships, family ties, productive performance of activities, satisfaction of basic social needs were identified and validated.
Keywords: social-psychological adjustment; ex-servicemen; socialization; individualization; self-efficacy; self-actualization; self-fulfilment; emotional stability; social values